What is the origin of the Italian term “medico competente”? - Riva, Michele Augusto; Carnevale, Francesco (La Medicina del Lavoro, 2017)
Background: The meaning of the term “medico competente” – usually adopted in Italy to indicate the occupational physician – is little known. Objectives: To describe the origins of the word “medico competente” in Italy. Methods: We conducted a comprehensive analysis of the Italian legislation from the end of the nineteenth century to the present day. Results: In the United Kingdom, occupational physicians were originally named as “certifying surgeon” (1833) and “appointed surgeon” (1860). In Italy, the term “medico delegato” was introduced to indicate the physician who visited child laborers (1886), while the word “medico competente” was first used in some propaganda leaflets of the Clinica del Lavoro of Milan in 1910. This term was officially used in Italian legislation in 1927 and was preferred to “medico di fabbrica” (factory physician) in the post-World War II period. Since 1982, the term “medico competente” has started to be considered as a synonym of occupational physician in Italian laws. Conclusions: The name “medico competente” appears to derive from a legislative imposition rather than from a voluntary choice developed in a medical and scientific context. Nowadays, Italian occupational physicians should be stimulated to find scientific, ethical, and professional meanings in this term, so helping to enhance their figure in modern society